Uneven Staining in Automated Immunohistochemistry: Cold and Hot Zones and Implications for Immunohistochemical Analysis of Biopsy Specimens. Issue 5 (May 2018) - Cheung, Carol C.; Swanson, Paul E.; Nielsen, Søren; Vyberg, Mogens; Torlakovic, Emina E.
Abstract : Objectives: The occurrence of uneven staining (UES) in automated immunohistochemistry (IHC) has been experienced by clinical laboratories and has the potential to confound readout, interpretation, and reporting of IHC assays despite the presence optimally stained on-slide controls. However, there are no studies of this phenomenon in regard to the type, frequency, and association with different automated IHC platforms. We studied the occurrence of UES in automated IHC assays with real world examples from clinical practice and by using a laboratory developed methodology to monitor baseline and periodic performance of automated IHC instruments. Materials and Methods: Sections of formalin-fixed, paraffin-embedded normal liver tissue were mounted on 180 glass slides and stained for HepPar1 on 6 automated IHC instruments (4 different models from 3 different manufacturers). Macroscopic and microscopic defects of staining were recorded. Results: Only 8% of slides showed completely uniform staining. UES, including areas of both increased and decreased staining, occurred with all instruments. Decreased staining was often zonal, involving large regions of the slide. Decreased staining mostly localized in an instrument-dependent manner. Increased staining tended to occur in small foci with a random distribution. Conclusions: The common occurrence of UES (particularly decreased staining) has important implications for the reliable read-out of IHC assays on biopsy samples. Baseline and periodic quality assurance testing for UES is recommended for all automated IHC instruments.